PENGARUH PERILAKU KOMUNIKASI TERHADAP SIKAP DAN ADOPSI TEKNOLOGI BUDIDAYA BAWANG MERAH DI LAHAN PASIR PANTAI KECAMATAN SANDEN KABUPATEN BANTUL - Wahyu Aji Sasongko (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
This research was conducted in Sanden subdistrict Bantul district with the purpose of finding out: 1) the communication behavior of onion farmers, 2) factors affecting communication behaviour, 3) factors affecting farmer’s attitude, and 4) the influence of communication behavior, attitude, and other factors, toward technology adoption of onion cultivation.The method used in this research was descriptive approach by survey technique. The sampling of village and farming groups were done purposively, while the sampling of respondent farmers was done randomly. The number of total sample was 60 farmers consisted of 30 farmers from Manunggal Farming Group, Srigading Village, and 30 farmers from Karang Rejo Farming Group, Gadingharjo Village. The analysis methods used were proportion test and multiple linier regression analysis.The result of this research showed that farmer’s communication behavior belonged to low category. The credibility of communication media positively affected toward farmer’s communication behavior, while education, land size, and motivation didn’t have significant affect. Communication behavior, motivation, dan education positively affected toward farmer’s attitude, while land size didn’t have significant affect. Farmer’s attitude positively affected toward technology adoption of onion cultivation, communication behavior, motivation, education, dan land size didn’t have significant affect. Communication behavior affected toward attitude and furthermore attitude affected toward technology adoption of onion at sandy coastal land.